Anxiety on quiet eye and performance of youth pistol shooters - Shah, E. J.; Chow, J. Y.; Lee, M. J. C. (Journal of Sport & Exercise Psychology, 2020)
In adults, longer quiet-eye (QE) durations have been associated with more successful sport performances and less deterioration in skill during anxiety-inducing situations. This study aimed to establish if QE patterns in youth are similar to those reported in adults. Ten youth shooters, age 13.13 ± 0.83 years, completed an air-pistol task under a control and an anxiety condition. Mixed-design 2 (performance outcome) × 2 (condition) ANOVA tests were conducted with two performance measures—objective and coach rated. No significant main or interaction effects were found. Unlike in adults, performance and anxiety did not differentiate QE duration in youth athletes, although QE duration was longer during good shots than poor shots across both performance measures, and the shortest durations were recorded during poor shots in the anxiety condition. This preliminary exploration encourages more research with youth athletes to determine the efficacy of QE patterns across different learners.